2000
DOI: 10.1073/pnas.180328897
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the ubiquitin-proteasome pathway with a cytosolic oligopeptidase activity

Abstract: Cytosolic proteolysis is carried out predominantly by the proteasome. We show that a large oligopeptidase, tripeptidylpeptidase II (TPPII), can compensate for compromised proteasome activity. Overexpression of TPPII is sufficient to prevent accumulation of polyubiquitinated proteins and allows survival of EL-4 cells at otherwise lethal concentrations of the covalent proteasome inhibitor NLVS (NIP-leu-leu-leu-vinylsulfone). Elevated TPPII activity also partially restores peptide loading of MHC molecules. Purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
118
1
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 37 publications
7
118
1
2
Order By: Relevance
“…Proteolytic activity was monitored by the increased fluorescence resulting from the release of the AMC group (excitation/emission 380/440 nm). A total of 4 nmol peptide RU1 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] was incubated with 12 l fractions 29, 31, and 32, respectively, for 20 min at 37°C. The digestion was stopped with 2% TFA and analyzed by MS as above.…”
Section: Protein Purificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Proteolytic activity was monitored by the increased fluorescence resulting from the release of the AMC group (excitation/emission 380/440 nm). A total of 4 nmol peptide RU1 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] was incubated with 12 l fractions 29, 31, and 32, respectively, for 20 min at 37°C. The digestion was stopped with 2% TFA and analyzed by MS as above.…”
Section: Protein Purificationmentioning
confidence: 99%
“…Earlier work, using the precursor peptide RU1 24 -47 , demonstrated that the exact C terminus of the antigenic peptide was directly produced by purified standard proteasome, but that the N terminus always carried additional 3 (RU1 [31][32][33][34][35][36][37][38][39][40][41][42] ) and 5 (RU1 29 -42 ) aa (16) (data not shown). This suggested that other peptidases might be necessary to trim the N-terminal extensions to the final nonamer RU1 34 -42 .…”
Section: Tpp II Mediates the Initial Trimming Of Ru1 29 -47 Precursormentioning
confidence: 99%
See 3 more Smart Citations